Anxiety in families of individuals with neurodevelopmental conditions in the early months of the COVID-19 pandemic in Switzerland - Di Poi, Giona; Dukes, Daniel; Meuleman, Ben; Banta Lavenex, Pamela; Lavenex, Pierre; Papon, Anouk; Tran, Michel; Stallmann, Lina; Treichel, Noémie; Samson, Andrea C. (Frontiers in Education, 2023)
In the spring of 2020, the COVID-19 pandemic generated a health, social, political, and economic crisis that dramatically reduced the institutional support for families of individuals with neurodevelopmental conditions (NDCs). To understand how these families may have experienced and coped with the pandemic, we created an online questionnaire that reached more than 10,000 families in 78 countries. The present study, framed within the International Classification of Functioning, Disability and Health (ICF-10) model, investigates the impact of specific health conditions and personal or environmental factors on the well-being of these families in Switzerland. In the current manuscript, we focus on findings concerning anxiety during the early months of the pandemic. To assess how differences in anxiety over time were predicted by specific health conditions or personal and environmental factors, two separate multilevel analyses were conducted for parents and their children with NDCs (N = 256). First, results showed that only parents reported an increase in anxiety when the pandemic started. Second, concerns related to loss of institutional support and financial and economic problems were the most anxiety-provoking factors for parents, whereas parents reported that the most anxiety-provoking factor for children was their concern about becoming bored. Third, a bidirectional effect was found between overall parental anxiety and reported overall anxiety of individuals with NDCs, showing potential emotional convergence among family members. Fourth, we present some transdiagnostic findings that may prove noteworthy in suggesting future research directions on the psychological impact of the pandemic and specific strengths and needs of individuals with NDCs in times of crisis and social estrangement. Finally, we present a series of reflections and practical suggestions that could help guide policymakers in potential future periods of crisis, social estrangement, and distance learning.